Erectile Dysfunction after Conservative Treatment of Sacral Fractures in Males without Injury to the Urinary System - Bayrak, Alkan; Duramaz, Altug (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Background This study aimed to determine the incidence of erectile dysfunction (ED) reported by patients, and to define the prognostic relationship between ED and conservatively treated sacral fracture without urethral injury.Methods Patients aged between 20 – 50 years who were sexually active and had no known sexual dysfunction prior to the trauma were included in the study. Seventy-seven patients (47 married, 30 single) treated conservatively for sacral fracture between April 2012 and February 2017 were retrospectively screened. Patients were compared in terms of age, marital status, body mass index (BMI), trauma mechanism, additional system injury, functional outcomes, and complications. Functional outcomes were assessed using the International Index of Erectile Function (IIEF-5) and the Majeed pelvic fracture functional assessment scale (MPS).Results No statistically significant difference was observed between fracture types with respect to age, BMI, follow-up, marital status, trauma mechanism, and accompanying injury. The incidence of ED was 27.3% for those that received conservative treatment after sacrum fracture. The mean score of IIEF-5 was 18.6 ± 6.6 and MPS was 77.2 ± 13.2. There was no significant relationship between the injury type of the patients and the IIEF-5 and MPS scores (p = 0.593 and p = 0.907, respectively). The lowest IIEF-5 score was found in Denis type 2 fractures (p = 0.020).Conclusion The frequency of ED was higher in Denis type 2 sacrum fractures. Sexual function should be questioned in the follow-up, especially in those fracture types.
Keywords: erectile dysfunction; sacrum fractures; conservative treatment